Screening Coconut Cultivars for Tolerance to Infestation by the Coconut Mite, Aceria guerreronis (Keifer) in Sri Lanka - Perera, Lalith; Sarathchandra, S. R.; Wickramananda, I. R. (International Coconut Community Journal, 2013)
The coconut mite (Aceria guerreronis Keifer) is a tiny pest which severely damages the nuts of the coconut palm (Cocos nucifera Linnaeus). At present there is no appropriate control method for this pest in Sri Lanka. Field observations have revealed difference in the severity of A. guerreronis mite infestation among selected and improved coconut cultivars in Sri Lanka. This difference has not been studied in depth and therefore the present study was conducted to investigate the levels of tolerance in selected and improved coconut cultivars and, if differences were demonstrated, to understand the mechanism behind the tolerance. A replicated trial in Thammenna Estate (TE) in Puttalam district in Sri Lanka, where the mite infestation was natural and severe, was selected for this study. The trial was planted in 1983 and consisted of two improved coconut cultivars; Sri Lanka Yellow Dwarf x Sri Lanka Tall (YDT) and Sri Lanka Green Dwarf x Sri Lanka Tall (GDT) and the selected Sri Lanka Tall cultivar (TT) which has, green (TTG) and russet coloured (TTR) forms. Population assessment of mites on immature nuts, damage initiation of the fourth bunch and harvest records were obtained. Further, characters that were thought to influence tolerance, such as nut shape as measured by ratio of length to breadth, the tightness of perianth to the nut surface and some changes in the affected tissues were also recorded. Yield data were collected for each cultivar to estimate the crop loss due to coconut mite damage. The results revealed that out of the cultivars tested in this trial, YDT had the lowest incidence of mite colonization and the smallest mite population size and symptom initiation compared to others. The distance between the perianth and nut surface, the least in YDT, is suggested as the most probable morphological feature that would impart tolerance to mite infestation.